VALIDITAS PENGEMBANGAN PENUNTUN PRAKTIKUM ILUSTRATIF MIKROTEKNIK HEWAN BERBASIS GUIDED INQUIRY - Mustami, Muhammad Khalifah (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2017)
The process of developing this study using the model of Dick & Carey. This study aims to product guiding animals microtechnic illustrative based on guided inquiry is valid, effective, and practical. Student education research subject is Biology 2014 class of fourth semester of the academic year 2015/2016. The instruments used in the form of sheet guiding practical validity. Based on the assessment of the product validator developed practical guides valid criteria with a value of 4.34 on aspects of validity were developed.Keywords: Practical Illustrative, Guided Inquiry, Microtechnic Animals